Early-Life Soy Exposure and Gender-Role Play Behavior in Children. - Adgent, Margaret A.; Daniels, Julie L.; Edwards, Lloyd J.; Siega-Riz, Anna Maria; Rogan, Walter J. (Environmental Health Perspectives, 2011)
BACKGROUND: Soy-based infant formula contains high levels of isoflavones. These estrogen-like compounds have been shown to induce changes in sexually dimorphic behaviors in animals exposed in early development. OBJECTIVE: We examined gender-role play behavior in relation to soy-based and non-soy-based infant feeding methods among children in the Avon Longitudinal Study of Parents and Children. METHODS: We studied 3,664 boys and 3,412 girls. Four exposure categories were created using data from questionnaires administered at 6 and 15 months postpartum: primarily breast, early formula (referent), early soy, and late soy. Gender-role play behavior was assessed using the Pre-School Activities Inventory (PSAI). Associations between infant feeding and PSAI scores at 42 months of age were assessed using linear regression. Post hoc analyses of PSAI scores at 30 and 57 months were also conducted. RESULTS: Early-infancy soy use was reported for approximately 2% of participants. Mean [95% confidence interval (CI)] PSAI scores at 42 months were 62.3 (62.0, 62.6) and 36.9 (36.6, 37.2) for boys and girls, respectively. After adjustment, early soy (vs. early formula) feeding was associated with higher (less feminine) PSAI scores in girls (β = 2.66; 95% CI: 0.19, 5.12) but was not significantly associated with PSAI scores in boys. The association between soy exposure and PSAI scores in girls was substantially attenuated at 30 and 57 months. CONCLUSIONS: Although not consistent throughout childhood, early-life soy exposure was associated with less female-typical play behavior in girls at 42 months of age. Soy exposure was not significantly associated with play behavior in boys.